Project-Based Learning as a Catalyst for Enhancing 21st-Century Skills in Secondary Education - Alya Nabila Adistia; Shavira Salsabila; Ismaul Fitroh; Achmad Afif Fikri; Muhammad Zia Alghar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examined the effectiveness of Project-Based Learning (PBL) in enhancing secondary students’ 21st-century skills using a quasi-experimental mixed-methods design. Participants were Grade 10–11 students from two comparable public schools, with intact classrooms assigned to a PBL condition or conventional instruction. Quantitative data were collected through pre-test and post-test measures of critical thinking, creativity, collaboration, communication, and self-regulation, while qualitative evidence was obtained from classroom observations, reflective journals, and semi-structured interviews. Statistical analyses indicated significantly higher post-test gains in the PBL group, with effect sizes suggesting meaningful educational impact across multiple skill domains. The qualitative strand revealed that skill growth was mediated by scaffolding practices, authentic task structures, iterative revision cycles, and group accountability mechanisms. Transferability and sustainability outcomes were strongest when assessment criteria valued process indicators and when projects were connected to real-world issues. The integration of findings suggests that PBL supports equitable skill development by providing multiple participation pathways for diverse learners. Implications for curriculum and teacher development are discussed.